Stapled vs hand suture closure of loop ileostomy: a meta‐analysis. (24th October 2013) - Gong, J.; Guo, Z.; Li, Y.; Gu, L.; Zhu, W.; Li, J.; Li, N.
Abstract: Aim: Loop ileostomies are widely used in colorectal surgery to reduce the consequences of distal anastomotic failure. The optimal surgical technique for their closure has yet not been defined. A meta‐analysis was performed to compare the outcome after stapled or hand sutured ileostomy closure. Method: An electronic literature search of EMBASE, PubMed and the Cochrane Library was undertaken to identify studies reporting stapled and hand sutured ileostomy closure. End‐points included postoperative small bowel obstruction (SBO), anastomotic leakage, wound infection, overall postoperative complications, operation time, hospital stay and surgery‐related cost. Results: Fourteen studies including 5084 patients were identified. Meta‐analysis showed that stapled closure was associated with a lower rate of SBO overall (OR = 0.56, P < 0.00001) and early (within 30 days of closure) SBO (OR = 0.51, P < 0.00001). This difference persisted for direct ileostomy closure (OR = 0.62, P = 0.02) or closure with bowel resection and hand sewn anastomosis (OR = 0.44, P < 0.00001). Stapled closure required a shorter inpatient stay (mean difference −1.22, P < 0.0001) and operating time (mean difference −11.21, P = 0.01). No significant difference was noted between the two techniques in terms of anastomotic leakage, wound infection, overall complications or cost. Conclusion: Stapled side‐to‐side anastomosis is associated with fewer complications, especially SBO, than hand sewn ileostomy closure by direct suture or resection and anastomosis. It is quicker to perform and associated with fewer postoperative bowel obstructions.